Microbial Contamination of Glaucoma Eyedrops Used by Patients Compared With Ocular Medications Used in the Hospital. Issue 8 (February 2015) - Teuchner, Barbara; Wagner, Julia; Bechrakis, Nikolaos E.; Orth-Höller, Dorothea; Nagl, Markus
Abstract : Abstract: The aim of this study was to compare the percentage of contamination of multiuse eyedrops applied by glaucoma patients at home and by the medical personnel at the outpatient department, the ward, and the operating room of our Department of Ophthalmology. Eyedrops were collected over a period of 11 months. Samples were taken from the dropper tip (smear), drops, and the residual fluid inside the bottle and cultivated on blood agar. Colony forming units were counted and identified by mass spectrometry. The percentage of contamination was significantly higher in eyedrops applied by the patients (29/119; 24.4%, P  < 0.01), used in the ward (26/133; 19.5%, P  < 0.01), and in the outpatient unit (6/35; 17.1%, P  = 0.036) compared with that in the operating room (6/113; 5.3%). The median period of use was 1 week in the operating room compared with 4 weeks in the other groups ( P  < 0.01). Glaucoma medications were significantly more frequently contaminated than antibiotic and anesthetic eyedrops ( P  < 0.05). For eyedrops applied by the patients, the tip was more frequently contaminated than the drops and the residual internal fluid. For eyedrops from the ward, the opposite was true. Pathogenic strains ( Pseudomonas aeruginosa, Serratia marcescens, Acinetobacter lwoffii, Stenotrophomonas maltophilia, and Staphylococcus aureus ) were found only in 6 bottles (1.5%), whereas most of the detected microbes belonged to human or environmental flora. This study underlines the importance of hygienic handling of eyedrops and raises the question of whether single-use glaucoma medication might be preferred to reduce the risk of contamination.